On the present state of the law and practice in Ireland with respect to wills and the administration of assets - Lawson, James A. (Dublin Statistical Society, 1852)
I beg leave to submit to you the following report upon the question proposed to me for investigation; namely, "The Present State of the Law and Practice in Ireland with respect to Wills, with a view to have all wills proved and registered at the domicile of the deceased, and to have the jurisdiction with respect to legacies, devises, the administration of assets, and the validity of wills consolidated and vested in the same Court."
Keywords: Wills; Stamp duty; 314.15